Dificultades en el aprendizaje escolar Aportes para una discusión integral - TALLIS, Jaime (MIÑO Y DAVILA, 1986)
Otros autores: MINOTTI, H.; TULA, R.; GARCIA RUDI, C.; VALLEJOS, M.; REBOIRAS, J.C.; FASCE, J.; RUVINSKY, R.; SCHLEMENSON DE ONS, S.